Analysis of Learning Obstacle Materials of KPK and FPB In Class V Elementary School Student Using Rasch Model Analysis - Maelani, Maelani; Supriadi, Supriadi (Didaktika, 2021)
Mathematics is a subject related to daily activities. For students, this subject is the most difficult. The material in question is about the Lowest Common Multiple (LCM) and Highest Common Factor (HCF) Based on the results of interviews with class teachers, students' grades are low in this material. This difficulty causes learning obstacles. One of the obstacles experienced was being confused when working on questions about the KPK and FPB which did not match the examples from the teacher and the difficulty of mastering the concept of factoring which was related to arithmetic operations. This is evidenced by the daily test scores from this material, namely from 28 children there are 14 people whose scores are below the KKM. So, it is important to make efforts to overcome this learning obstacle. Furthermore, the research was carried out to know student barriers, knowing the factors causing this learning obstacle, and knowing the level of difficulty of the questions for using the Rasch Model analysis. This study uses a qualitative approach with a quantitative descriptive method involving 28 students and teachers to take tests and interviews related to this material. The data analysis in this research uses the Rasch Model with the help of the Winstep software version 4.5.2. The results of this study indicate that the Rasch Model analysis for the learning obstacle on this material tends for students' abilities to be smaller than the level of difficulty of the questions